1989
DOI: 10.1159/000125092
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Modification of Ovine Pineal Function

Abstract: The results of a seasonal study of the regulation by steroids of ovine pineal β-adrenoceptors are reported. The effects of ovariectomy, steroid implants and superior cervical ganglionectomy were investigated in Merino ewes. The results confirm earlier observations showing a seasonal variation in the sensitivity of the receptors to modification by gonadal steroids. A marked difference in receptor density and affinity between the follicular and luteal phases of the estrous cycle is shown for the first time, a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The exact method by which the duration of elevated melatonin induces or inhibits reproduction remains obscure [Malpaux et al, 1987;1988b;Pelletier and Thimonier, 19871 because, in sheep, this nightly rise does not always correspond to the duration of the scotophase [Rollag et al, 1978a;Lincoln et al, 1981;Almeida and Lincoln, 1984;Guerin et al , 19891. Since there are reports indicating no seasonal changes in amplitude of the nightly rise of melatonin [Arendt et al, 198 1;Rollag et al, 1978b;Kennaway et al, 1983;Bittman et al, 1983b;Rodway et al, 1985;Guerin et al, 1989;Maxwell et al, 19891 it has been suggested that amplitude of the nightly rise in melatonin does not intluence reproduction in sheep [Karsch et al, 1988;Guerin et al, 19891. Interestingly, most of the studies to characterize the seasonal patterns of endogenous melatonin secretion in sheep have used relatively long intervals [ 1-3 hr] between samples [Arendt et al,198 1 ; Kennaway et al, 1983;Rodway et al, 1985;Maxwell et al, 1989;Guerin et al, 19891, preclud-ing the possibility of detecting the rapidly changing melatonin levels observed in more frequently collected samples from sheep [Rollag et al, 1978a,b;Bittman et al, 1983a;Cozzi et al, 19881, humans [Rivest et al, 1989;Trinchard-Lugan and Waldhauser, 19891 and rabbits [Chan et al, 19901. Therefore, this study was initiated to investigate the seasonal changes in melatonin profiles determined from frequently collected samples from adult rams.…”
Section: Introductionmentioning
confidence: 99%
“…The exact method by which the duration of elevated melatonin induces or inhibits reproduction remains obscure [Malpaux et al, 1987;1988b;Pelletier and Thimonier, 19871 because, in sheep, this nightly rise does not always correspond to the duration of the scotophase [Rollag et al, 1978a;Lincoln et al, 1981;Almeida and Lincoln, 1984;Guerin et al , 19891. Since there are reports indicating no seasonal changes in amplitude of the nightly rise of melatonin [Arendt et al, 198 1;Rollag et al, 1978b;Kennaway et al, 1983;Bittman et al, 1983b;Rodway et al, 1985;Guerin et al, 1989;Maxwell et al, 19891 it has been suggested that amplitude of the nightly rise in melatonin does not intluence reproduction in sheep [Karsch et al, 1988;Guerin et al, 19891. Interestingly, most of the studies to characterize the seasonal patterns of endogenous melatonin secretion in sheep have used relatively long intervals [ 1-3 hr] between samples [Arendt et al,198 1 ; Kennaway et al, 1983;Rodway et al, 1985;Maxwell et al, 1989;Guerin et al, 19891, preclud-ing the possibility of detecting the rapidly changing melatonin levels observed in more frequently collected samples from sheep [Rollag et al, 1978a,b;Bittman et al, 1983a;Cozzi et al, 19881, humans [Rivest et al, 1989;Trinchard-Lugan and Waldhauser, 19891 and rabbits [Chan et al, 19901. Therefore, this study was initiated to investigate the seasonal changes in melatonin profiles determined from frequently collected samples from adult rams.…”
Section: Introductionmentioning
confidence: 99%